2016
DOI: 10.4038/cmj.v61i1.8261
|View full text |Cite
|
Sign up to set email alerts
|

Psychological morbidity and illness perception among patients receiving treatment for tuberculosis in a tertiary care centre in Sri Lanka

Abstract: A descriptive cross sectional study was carried out to determine prevalence of depression and anxiety and to describe disease perception among patients with tuberculosis (TB) at National Hospital for Respiratory Diseases (NHRD), Welisara. Consecutive patients on anti-TB therapy admitted to wards and attending clinic were recruited until the estimated sample of 430 was reached. They were assessed using Hospital Anxiety and Depression Scale (HADS) and Brief Illness Perception Questionnaire (BIPQ). A total of 254… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 6 publications
(9 reference statements)
1
9
0
Order By: Relevance
“…The prevalence of depression in our study population was similar to the prevalence of depression reported among patients attending an outpatient department of a tertiary care hospital, Colombo (17). In comparison to our study, the prevalence of anxiety (17.6%) was similar and depression (8.5%) was lower in a previous study of clinic follow up patients with tuberculosis, conducted at the same hospital using the same rating scale (18).…”
Section: Discussionsupporting
confidence: 86%
“…The prevalence of depression in our study population was similar to the prevalence of depression reported among patients attending an outpatient department of a tertiary care hospital, Colombo (17). In comparison to our study, the prevalence of anxiety (17.6%) was similar and depression (8.5%) was lower in a previous study of clinic follow up patients with tuberculosis, conducted at the same hospital using the same rating scale (18).…”
Section: Discussionsupporting
confidence: 86%
“…In the review of literature, there were several studies evaluating illness perceptions of TB. The BIPQ scores of a multicenter study[5] from Europe and Asia between 2008 and 2011 and a single-center study[19] from Sri Lanka between 2014 and 2015were 36.3 ± 11.1 and 27.4 ± 14.4, respectively, indicating that illness perception varies depending on socio-demographic and geographic backgrounds. However, these two studies revealed that concern had the most threatening view among the BIPQ items, similar to our study.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, we did not assess other variables that were known to be associated with illness perception. For example, depression and anxiety, which are common in TB patients, influence illness perception[19,24]. Another study identified positive correlations between quality of life and illness perception among TB patients[25].…”
Section: Discussionmentioning
confidence: 99%
“…The elderly describing their health status as good perceived their illness as less troublesome. Galhenage et al (2016) studied psychological morbidity and illness perception among TB patients in Sri Lanka. Their results show that illness-related depression and anxiety are common among the above patients.…”
Section: Discussionmentioning
confidence: 99%